Identification and Construction of a Predictive Immune-Related lncRNA Signature Model for Melanoma - Li FW (Dove Medical Press, 2021)
Fang-Wei Li, Sheng-Kang Luo Department of Plastic and Reconstructive Surgery, Guangdong Second Provincial General Hospital, Guangzhou City, Guangdong Province, 510317, People’s Republic of ChinaCorrespondence: Sheng-Kang LuoDepartment of Plastic and Reconstructive Surgery, Guangdong Second Provincial General Hospital, 466 Middle Xin Gang Road, Guangzhou City, Guangdong Province, 510317, People’s Republic of ChinaTel +8615626045022Email luoshk@gd2h.org.cnObjective: The occurrence and development mechanisms of melanoma are related to immunity and lncRNAs. Therefore, it is necessary to systematically explore immune-related lncRNA profiles to help improve the prognosis of melanoma.Methods: We integrated immune-related lncRNAs and the basic clinical information of melanoma patients in the TCGA dataset. Immune-associated lncRNAs were selected by differential expression screening and enriched for analysis. After univariate and multivariate Cox regression analyses, a new prognostic indicator based on immune-associated lncRNAs was established.Results: Overall, differentially expressed immune-related lncRNAs were significantly associated with clinical outcomes in patients with melanoma. A prognostic model was then established based on 14 immune-associated lncRNAs (LRRC8C-DT, AC021188.1, MALINC1, CCR5AS, EIF2AK3-DT, AC022306.2, AC242842.1, AL034376.1, AL662844.4, AC009065.3, AC099811.3, AC125807.2, SPINT1-AS1 and AC009495.2). Melanoma patients in the high-risk group had worse overall survival than those in the low-risk group. The AUC of the risk score was 0.786.Conclusion: This study identified several clinically significant immune-related lncRNAs and established a relevant prognostic model, which provided a molecular analysis of immunity in melanoma and potential prognostic lncRNAs for melanoma.Keywords: lncRNA, immune-related, model, overall survival, melanoma